PSYCHOANALYTIC ANALYSIS OF MENTAL DISORDERS AND CHARACTER RELATIONSHIPS IN THE TV SERIES “HANNIBAL” SEASON I - Catur Yuliani; Ika Oktaria Cahyaningrum; I Desak Ketut, Titis Ary Laksanti (Acceleration: Multidisciplinary Research Journal, 2025)
This study analyzes the characterization and psychoanalytic dynamics of two main characters in the Hannibal TV Series Season I: Hannibal Lecter and Will Graham. Using Freud’s psychoanalytic theory—specifically the concepts of Id, Ego, and Superego—the research applies a descriptive qualitative method. Data were collected from selected scenes and dialogues to interpret character traits and the psychological relationship between the two. The characterization is presented through both “showing” and “telling” techniques in the narrative. These methods help reveal the internal psychological drives influencing each character. The analysis finds that Hannibal is primarily driven by the Id, often ignoring the functions of the Ego and Superego. This leads him to act impulsively, manipulatively, and without moral restraint. In contrast, Will Graham demonstrates a stronger influence of Ego and Superego, showing moral awareness and rational judgment, though his psychological stability is gradually eroded due to Hannibal’s manipulation. The results indicate that Hannibal holds psychological dominance in the relationship. His Id-driven behavior allows him to control and reshape Will’s perception and emotional state. This research contributes to the understanding of how psychoanalytic elements can influence character development and interpersonal dynamics in visual media narratives.